Design an Alumni Data Collection Information System Using the Waterfall Method - Dwi Rahmayani Early; Alhuda Alhuda (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The background of this research is that there is no alumni data collection information system at the Informatics and Computer Engineering Education Department (PTIK) IAIN Bukittinggi. Because the PTIK department already has a large number of alumni, a system that can serve as a forum for alumni data is required. The method used is Research and Development (R&D). R&D is a research method used to manufacture a specific product and test its effectiveness. The development model used is ADDIE, which stands for analyze, design, develop, implement, evaluate. The waterfall model is used in the system development model. The findings of this study include the development of an information system for collecting alumni data. The product is available for use by the head of PTIK department and the alumni. To demonstrate the system's effectiveness, three validators were obtained with a total value of 0.76 and were declared valid, while three examiners obtained a total value of 86.7 and were declared very practical. The effectiveness test on 5 graduates yielded a total score of 0.88 using very effective criteria.